Pemberdayaan Perempuan (Penganyam) Rawan Sosial Ekonomi di Kecamatan Pantai Cermin - Syndi Febriani; Fajar Utama Ritonga; Berlianti Berlianti (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
Casework is a process used by humanitarian service agencies to assist individuals in addressing social functioning issues. This process includes several stages: engagement, assessment, planning, intervention, evaluation, and termination. This study examines the application of the casework method with a client named SM, a 30-year-old widow with two children facing economic and social limitations. Through interviews and observations using the BPSS (Bio, Psycho, Social, Spiritual) approach, the practitioner assessed the client’s condition, revealing that SM struggled with economic difficulties and challenges in providing adequate care for her children. In the intervention stage, SM was provided with a program to develop weaving skills, which led to the production of woven mats, curtains, and decorations. Monitoring was conducted to ensure that the client adhered to the program, ultimately increasing SM’s income to Rp 40,000 per day. In the termination stage, the cooperation between the practitioner and the client was concluded as the agreed-upon goals had been achieved. This study demonstrates that with the right approach, individuals facing social and economic limitations can develop their potential and improve their well-being.